DISTRIBUIÇÃO POTENCIAL DA PIAVA, Megaleporinus obtusidens (VALENCIENNES, 1847), NA BACIA PARANÁ-PARAGUAI - SOUZA, Beatriz Cristina de Paula; BAILLY Dayani; RÉ Reginaldo; BATISTA-SILVA, Valéria Flávia (ANAIS DO ENIC, 2023)
-